Socio-demographic variation in stage at diagnosis of breast, bladder, colon, endometrial, lung, melanoma, prostate, rectal, renal and ovarian cancer in England and its population impact - Barclay, M. E. (Br J Cancer, 2021)
BACKGROUND: Stage at diagnosis strongly predicts cancer survival and understanding related inequalities could guide interventions. METHODS: We analysed incident cases diagnosed with 10 solid tumours included in the UK government target of 75% of patients diagnosed in TNM stage I/II by 2028. We examined socio-demographic differences in diagnosis at stage III/IV vs. I/II. Multiple imputation was used for missing stage at diagnosis (9% of tumours). RESULTS: Of the 202,001 cases, 57% were diagnosed in stage I/II (an absolute 18% ‘gap’ from the 75% target). The likelihood of diagnosis at stage III/IV increased in older age, though variably by cancer site, being strongest for prostate and endometrial cancer. Increasing level of deprivation was associated with advanced stage at diagnosis for all sites except lung and renal cancer. There were, inconsistent in direction, sex inequalities for four cancers. Eliminating socio-demographic inequalities would translate to 61% of patients with the 10 studied cancers being diagnosed at stage I/II, reducing the gap from target to 14%. CONCLUSIONS: Potential elimination of socio-demographic inequalities in stage at diagnosis would make a substantial, though partial, contribution to achieving stage shift targets. Earlier diagnosis strategies should additionally focus on the whole population and not only the high-risk socio-demographic groups.